Improving Guideline Compliance in Australia With a National Percutaneous Coronary Intervention Outcomes Registry - Eccleston, D.; Horrigan, M.; Rafter, T.; Holt, G.; Worthley, S.; Sage, P.; Whelan, A.; Reid, Christopher; Thompson, P. (Elsevier, 2016)
© 2017 Australian and New Zealand Society of Cardiac and Thoracic Surgeons (ANZSCTS) and the Cardiac Society of Australia and New Zealand (CSANZ).Background: Secondary prevention strategies after percutaneous coronary intervention (PCI) include statins and dual anti-platelet therapy, however there are significant gaps between guidelines and practice. Contemporary PCI practice requires comprehensive data collection to allow dynamic auditing and benchmarking of key performance and safety indices.Genesis HeartCare is Australia's largest collaborative venture of cardiologists, practising at over 40 public and private hospitals. We hypothesised that measurement and local reporting of data would improve patient outcomes through improving compliance with guideline therapies. Methods: Real-time benchmarking via a national clinical quality and outcomes register, the Genesis Cardiovascular Outcomes Registry (GCOR-PCI). GCOR-PCI prospectively collected clinical, procedural, medication and outcomes data for 6720 consecutive patients undergoing PCI from 10 private hospitals across Australia. Key performance outcomes benchmarked against the aggregated study cohort and international standards were reported to individual sites. The main outcome measure was compliance with guideline medications (statins, anti-platelet agents). Results: Early data identified specific practice patterns associated with lower rates of statin therapy post-PCI, which led to changes in practice. Between the first and latest year of data collection there was significant improvement in the rates of statin therapy at discharge (92.1 vs. 94.4% p<0.03) and 12 months post-PCI (87.0 vs. 92.2% p<0.001) and of antiplatelet therapy at 12 months (90.7 vs. 94.3% p<0.001). Conclusions: This large-scale collaboration provides a platform for the development of quality improvement initiatives. Establishment of this clinical quality registry improved patient care by identifying and monitoring gaps in delivery of appropriate therapies, driving key practice change.